The pocos de caldas hot spot: A big blast for nuclear energy in Brazil - Bonotto, Daniel Marcos [UNESP] (My University, 2010)
The importance of the radioactive minerals occurring at the Poços de Caldas plateau for the establishment of the Brazilian Nuclear Energy Program has been recognized worldwide. The interest in uranium in the present days as a consequence of its use as a nuclear fuel coupled to its price in the international market has lead to intense debate, mainly due to questions related to global warming. Thus, all initiatives/studies directed to a better knowledge/management of this element in the environment are welcome and needed. This book describes many results obtained on the analysis of natural radionuclides in different compartments, considering their distribution in (un)disturbed environments, as well as consequences of the anthropogenic actions and possible lessons that can be learned from the past uranium exploration activities held at the Poços de Caldas caldera. © 2010 by Nova Science Publishers, Inc. All rights reserved.